Niemann-Pick disease type C: a case series of Brazilian patients - Paulo José Lorenzoni; Elaine Cardoso; Ana C. S. Crippa; Charles Marques Lourenço; Fernanda Timm Seabra Souza; Roberto Giugliani; Maria Luiza Saraiva-Pereira; Salmo Raskin; Isac Bruck; Cláudia S. K. Kay; Rosana H. Scola; Lineu C.Werneck; et al. (Arquivos de Neuro-Psiquiatria)
The aim of the study was to analyze a series of Brazilian patients with Niemann-Pick disease type C (NP-C). Method Correlations between clinical findings, laboratory data, molecular findings and treatment response are presented. Result The sample consisted of 5 patients aged 8 to 26 years. Vertical supranuclear gaze palsy, cerebellar ataxia, dementia, dystonia and dysarthria were present in all cases. Filipin staining showed the “classical” pattern in two patients and a “variant” pattern in three patients. Molecular analysis found mutations in the NPC1 gene in all alleles. Miglustat treatment was administered to 4 patients. Conclusion Although filipin staining should be used to confirm the diagnosis, bone marrow sea-blue histiocytes often help to diagnosis of NP-C. The p.P1007A mutation seems to be correlated with the “variant” pattern in filipin staining. Miglustat treatment response seems to be correlated with the age at disease onset and disability scale score at diagnosis.